Prevalence and antimicrobial susceptibility of bacterial pathogens isolates from diseased swine in southwest, China - Xu-Ting Li; Bin Wang; Jin-Liang Li; Fu-Qiang Zeng; Xue Gong (African Journal of Pig Farming, 2014)
The purpose of this study was to investigate the prevalence of antimicrobial resistance in the clinical bacterial isolates from diseased swine in southwest, China during 2009-2010. A total of 504 bacterial isolates (19 species) were collected from the 364 clinical samples. The activity of 6-14 antibiotics to each bacterial species was examined. The sensitivity was tested by the disk diffusion method and performed according to CLSI guidelines in Mueller-Hinton agar. The most common pathogens were Escherichia coli (n=154; 30.56%), Staphylococcus spp. (n=110; 21.83%), Enterococcus faecalis (n=58; 11.51%), Klebsiella pneumoniae (n=44; 8.73%), Proteus mirabilis (n=43; 8.53%) and Streptococcus suis (n=30; 5.93%). All isolates revealed high level of resistance to ampicillin (47.6-100%), amoxicillin (52.6-100%), cephalothin (29-100%), norfloxacin (52.6-83.3%), gentamicin (45.1-83.3%) and terramycin (61.9-100%). Moreover, 93% of the isolates exhibited multiple drug resistance (MDR; resistance ≥ 3 antimicrobials). Only ticarcillin/clavulanate exhibited very high activity against E. coli (98.1%), Staphylococcus spp. (91.9%), K. pneumaniae (92.3%) and P. mirabilis (97.2%), respectively. These findings suggest that antimicrobial resistance of bacterial pathogens isolates is commonly present among diseased swine in Southwest, China, and they also suggest the need for more prudent use of antibiotics by farmers and veterinarians.